Gender Transformation and Social Mobility of The Malind Women: Tradition, Affirmative Action, and Meritocracy in Papua's Bureaucracy - Rosmayasinta Makasau; Ulfa Sevia Azni; Alfons No Embu; Karolus B. Bala; Luigi Pellizzoni; Eko Wahyono (Universitas Muhammadiyah Tangerang, 2025)
This study examines gender constructions and women’s leadership in traditional Malind society and analyses the social mobility mechanisms through which Malind women attain strategic posts in the Merauke Regency bureaucracy. Using a qualitative descriptive approach, data were generated through in-depth interviews, participant observation and document analysis. Findings indicate that, although traditional Malind culture organises gender and leadership along clearly patriarchal lines, recent shifts in social paradigms have widened access to education and public leadership for women. Malind women navigate bureaucratic structures by combining educational attainment, support from family and community, strong social and professional networks, and opportunities created by Papua's Special Autonomy framework. This framework affords affirmative recognition to Indigenous Papuans, including women, to hold government posts, while the civil services merit system continues to require high standards of competence and performance. The analysis shows that the interaction of cultural identity, affirmative action and meritocracy has enabled the rise of capable and respected female leaders in local government. These leaders demonstrate a transformative style that balances professionalism with empathy and collaboration, contributing to a more inclusive and equitable public administration in Papua. Penelitian ini bertujuan untuk mengkaji konstruksi gender dan kepemimpinan perempuan dalam masyarakat tradisional Malind, serta menganalisis mekanisme mobilitas sosial yang memungkinkan perempuan Malind mencapai posisi strategis dalam birokrasi Pemerintah Kabupaten Merauke. Dengan menggunakan pendekatan deskriptif kualitatif, data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen. Temuan menunjukkan bahwa meskipun budaya tradisional Malind menganut sistem patriarkal dengan pemisahan peran dan kepemimpinan berbasis gender yang tegas, perubahan paradigma sosial belakangan ini telah membuka akses yang lebih luas bagi perempuan untuk terlibat dalam pendidikan dan kepemimpinan publik. Perempuan Malind berhasil menavigasi struktur birokrasi dengan menggabungkan akses pendidikan, dukungan keluarga dan komunitas, jaringan sosial dan profesional, serta peluang yang diberikan oleh Undang-Undang Otonomi Khusus Papua. Undang-undang ini memberikan afirmasi bagi Orang Asli Papua (termasuk perempuan) untuk menduduki jabatan pemerintahan, meskipun sistem merit ASN tetap menuntut standar kompetensi dan kinerja yang tinggi. Studi ini menemukan bahwa sinergi antara identitas budaya, afirmasi, dan meritokrasi telah melahirkan pemimpin-pemimpin perempuan yang kompeten dan dihormati. Mereka menunjukkan gaya kepemimpinan transformatif yang menggabungkan profesionalisme, empati, dan kolaborasi, serta berkontribusi terhadap tata kelola pemerintahan yang lebih inklusif dan adil di Papua.